Guest Editorial Special Issue “Software Engineering” - Vasenin, V. A. (Programming and computer software, 2024)
This issue presents the results of the theoretical and applied researches conducted by the authors focused on the development and maintenance of complex software tools and systems at various stages of their life cycle.